Quality assessment of electronic business transactions B2B and B2C: an empirical study in companies of northern Greece - Στειακάκης Εμμανουήλ; Δριτσάκης Νικόλαος; Ιωαννίδης Στυλιανός (SPOUDAI Journal of Economics and Business, 2004)
The electronic service quality assessment along with the main quality factors in the area of electronic commerce, are reported herein. In particular, the quality assessment of electronic business transactions B2B and B2C when the assessment is done by the companies (and not by the customer), is undertaken by means of the SERVQUAL service quality model and its extended approach in electronic commerce (e-Service Quality). In the framework of these models, 10 quality criteria are suggested, which are grouped in categories according to the SERVQUAL dimensions, with corresponding impact factors. A sample of 142 companies of Northern Greece, which have already been in electronic business, is searched. The salient findings of this research are i) the definition of percent significance of the SERVQUAL dimensions and ii) the assessment of the suggested quality criteria, separately in B2B and B2C transactions. JEL Classification: M11, L15